Rationalization of costs by using the tool of the quality function deployment: / applied research in the State Company for Textile and Leather Industries (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The research aims to apply one of the techniques of management accounting, which is the technique of the quality function deployment on the men's leather shoe product Model (79043) in the General Company for Textile and Leather Industries by determining the basic requirements of the customer and then designing the characteristics and specifications of the product according to the preferences of the customer in order to respond to the customer's voice in agreement With the characteristics and technical characteristics of the product, taking into account the products of the competing companies to achieve the maximum customer satisfaction, the highest quality and the lowest costs. Hence, the importance of research has emerged, which indicates that the quality function deployment is a tool that achieves response to customer requirements because it is a customer-driven design tool, and thus contributes to achieving a competitive advantage, and from here the research problem has arisen in the necessity of applying management accounting tools (the quality function deployment tool) to improve the quality of design Product and cost optimization, responding to customer's voice, and achieving the company's competitive advantage , As for the most important conclusions reached by the research, it is represented by the weakness of the quality culture in the company, especially the "QFD" tool that is concerned with identifying and achieving the customer's requirements and expectations, as a result of the company's weak orientation towards focusing on the customer as well as the company's lack of interest in comparison with competitors. As for the most important recommendations that the research called for is necessary Adopting the application of the QFD tool due to its importance in achieving customers' desires as well as achieving cost rationalization, as well as the research recommended to involve the customer in the product design process, which has the effect of achieving product quality from the customer’s point of view, thus gaining long-term satisfaction and loyalty.